2020
DOI: 10.17516/1998-2836-0182
|View full text |Cite
|
Sign up to set email alerts
|

Solid Acid Catalysts Based on Niobium and Zirconium Oxides for Hydrolysis-Dehydration of Cellulose Into Glucose and 5-Hydroxymethylfurfural. Impact of Preparation Technique on Catalytic Properties

Abstract: The impact of the preparation techniques of niobium oxide and two-component systems based on niobium and zirconium oxides on the catalytic properties was studied in the one-pot hydrolysisdehydration of cellulose into glucose and 5-hydroxymethylfurfural. Cellulose transformation was performed in an autoclave at 180 °С under argon atmosphere. The most promising methods for the preparation of solid catalysts were found to be microwave heating and mechanical activation. Glucose and 5-hydroxymethylfurfural can be p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Materials based on niobium and zirconium oxides are of considerable interest in the processing of cellulose into 5-HMF due to the existing acid-base sites [19] and their high stability in hot water [23][24][25][26]. We previously investigated [27,28] one-pot hydrolysisdehydration of mechanically activated cellulose in pure hot water to produce glucose and 5-hydroxymethylfurfural in the presence of amorphous niobium oxide supported on a zirconium dioxide (NbO x /ZrO 2 ). It was found that activity of NbO x /ZrO 2 systems depended on the Nb 2 O 5 content and decreased as follows: 2.8%Nb/ZrO 2 ~1.1%Nb/ZrO 2 ZrO 2 > 0.5%Nb/ZrO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Materials based on niobium and zirconium oxides are of considerable interest in the processing of cellulose into 5-HMF due to the existing acid-base sites [19] and their high stability in hot water [23][24][25][26]. We previously investigated [27,28] one-pot hydrolysisdehydration of mechanically activated cellulose in pure hot water to produce glucose and 5-hydroxymethylfurfural in the presence of amorphous niobium oxide supported on a zirconium dioxide (NbO x /ZrO 2 ). It was found that activity of NbO x /ZrO 2 systems depended on the Nb 2 O 5 content and decreased as follows: 2.8%Nb/ZrO 2 ~1.1%Nb/ZrO 2 ZrO 2 > 0.5%Nb/ZrO 2 .…”
Section: Introductionmentioning
confidence: 99%